Logistic Distribution Centre’s - An Element Supporting the Activities of The Organization - Marian KOPCZEWSKI; Grzegorz WISNIEWSKI (Communications of International Proceedings, 2022)
The problem of organization and building efficiency in distribution centers is currently a significant aspect affecting both economic and military security of the local community, as well as countries and global regions. Building efficiency based on knowledge, constant improvement is the key here. The optimal organization of deliveries, combined with the conclusions drawn from the virtual organization, results in an advantage in the sea and land deliveries of raw materials. Organizations focused on economic, military and social success, after the implementation of the variables described in the article, exhibit features of competitive and military advantage. The race between the interested parties takes the form of combining the activities of science, business, and social associations, building the right, effective-oriented, intelligent facilities.
Keywords: logistics; distribution; organizations; support